PERSIAPAN PENSIUN KARYAWAN SWASTA RETAIL MELALUI PENINGKATAN LITERASI FINANSIAL, NIAT DAN PERILAKU MENABUNG - Ciputra, Kurniawati; Syah, Tantri Yanuar Rahmat (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this study is so that the gap between retirement age and life expectancy can still be prepared before retirement. This study uses a purposive sampling method and primary data collected from employees of private companies in the retail sector with manager level and below as many as 132 respondents located in Jakarta, Bogor, Tangerang, Depok, and other cities in Indonesia. Data were analyzed using the Structural Equation Model (SEM) with SmartPLS 4.0. The results of the study indicate that saving behavior has a significant impact on retirement financial planning. Private retail employees who save consistently are more likely to secure welfare in old age which confirms a strong correlation between saving habits and retirement planning. This study contributes to theoretical developments in multidisciplinary studies, especially finance and management, and as a reference for future research on financial behavior, retirement planning, and group behavior. This study implies that private employees without monthly pensions should prepare for retirement earlier to ensure a prosperous post-retirement life. Companies can support this by helping employees manage their income effectively. However, this research is still limited to private retail employees in a small number of locations in Indonesia.